Biogenic synthesis of reduced graphene oxide decorated with silver nanoparticles (rGO/Ag NPs) using table olive (olea europaea) for efficient and rapid catalytic reduction of organic pollutants. (January 2023) - Sun, Wen; Hong, Yaoliang; Li, Tian; Chu, Huaqiang; Liu, Junxia; Feng, Li; Baghayeri, Mehidi
Abstract: In this work, graphene oxide (GO) sheets were prepared via a facile electrochemical exfoliation of graphite in acidic medium and subsequent oxidation with potassium permanganate. The GO sheets were employed for preparation of reduced GO adorned with nanosized silver (rGO/Ag NPs) using green reduction of GO and Ag(I) via olive fruit extract as a reducing and immobilizing agent. The crystal phase, morphology, and nanostructure of the prepared catalyst were characterized by XRD, SEM, EDX, UV–Vis and Raman spectroscopy techniques. The as-prepared rGO/Ag NPs showed superior catalytic performance towards the complete reduction (up to 99%) of 4-nitrophenol (4-NPH) to 4-aminophenol (4-APH) and rhodamine B (RhB) to Leuco RhB within 180 s using NaBH4 at ambient condition. The rate constant (k) values were found to be 0.021 and 0.022 s −1 for 4-NPH and RhB reduction, respectively. In addition, the regenerated catalyst could be reused after seven cycles without losing any apparent catalytic efficiency. Accounting for the excellent catalytic capability, chemical stability and environment-friendly synthesis protocol, the rGO/Ag NPs has great potential working as a heterogeneous catalyst in the transforming harmful organic contaminants into less harmful or harmless compounds. Graphical abstract: Image 1 Highlights: Efficient reduction of 4-nitrophenol and rhodamine B using biosynthesized rGO/Ag NPs. The green synthesized nanocatalyst is reusable for 7 consecutive experimental cycles. A possible reduction mechanism was suggested.